The Plinko Bounce - Clark, Martin (Los Angeles, CA : Rare Bird Books, 2023)
For seventeen years, small-town public defender Andy Hughes has been underpaid to look after the poor, the addicted, and the unfortunate souls who constantly cycle through the courts, charged with petty crimes. Then, in the summer of 2020, he's assigned to a grotesque murder case that brings national media focus to rural Patrick County, Virginia--Alicia Benson, the wife of a wealthy businessman, is murdered in her home. The accused killer, Damian Bullins, is a cunning felon with a long history of violence, and he confesses to the police. He even admits his guilt to Andy. But a simple typographical error and a shocking discovery begin to complicate the state's case, making it possible Bullins might escape punishment. Duty-bound to give his client a thorough defense, Andy--despite his misgivings--agrees to fight for a not-guilty verdict, a decision that will ultimately force him to make profound, life-and-death choices, both inside and outside the courtroom.
new book 2023 fall.
Keywords: Public defenders -- Fiction; Political; Mystery and Detective; Small town and rural; Suspense fiction; Family life; Animals; Fiction; Thriller fiction